Sistem Kendali Pemberian Pakan Ayam Broiler Otomatis Berbasis Mikrokontroler - Tongkonoo, Agustian; Salihi, Irvan Abraham; Taliki, Sunarto (Teknik Informatika Fakultas Ilmu Komputer Universitas Ichsan Gorontalo, 2023)
ABSTRACT ; A control system is a system that produces a certain value as its output through controlling or changing the provisions of the system input. Feeding is an important element in determining the level of broiler production. Likewise, there is one farmer in Bilungala Village, Bone Pantai Subdistrict producing broiler chickens. Feeding chickens can be made easier by using a mechanical device controlled by equipment. This system uses a microcontroller connected to an Arduino and a timer for feeding chickens with a Real-Time Clock (RTC). This automatic tool has two parts, namely, the main container serves as a place to store food reserves and the second container as a place to feed the chickens. The Real-Time Clock functions to regulate the feeding hours of broilers. A Solenoid Valve functions as a faucet for feeding the broilers carried out from 07.00 through 17.00. It is for the morning, noon, and evening feedings regulated by the Real-Time Clock (RTC).Keywords: control system, chicken feeding, automatic, RTC (Real Time Clock), Solenoid Valve